P-POSSUM as mortality predictor in COVID-19-infected patients submitted to emergency digestive surgery. A retrospective cohort study. (December 2021) - Madrazo, Zoilo; Osorio, Javier; Videla, Sebastián; Sainz, Beatriz; Rodríguez-González, Araceli; Campos, Andrea; Santamaría, Maite; Pelegrina, Amalia; González-Serrano, Carmen; Aldeano, Aurora; Sarriugarte, Aingeru; Gómez-Díaz, Carlos Javier; et al.
Abstract: Background: COVID-19 infection is associated with a higher mortality rate in surgical patients, but surgical risk scores have not been validated in the emergency setting. We aimed to study the capacity for postoperative mortality prediction of the P-POSSUM score in COVID-19-positive patients submitted to emergency general and digestive surgery. Material and methods: Consecutive patients undergoing emergency general and digestive surgery from March to June 2020, and from March to June 2019 in 25 Spanish hospitals were included in a retrospective cohort study. Main outcome: 30-day mortality. P-POSSUM discrimination was quantified by the area under the curve (AUC) of ROC curves; calibration was assessed by linear regression slope ( β estimator); and sensitivity and specificity were expressed as percentage and 95% confidence interval (CI). Results: 4988 patients were included: 177 COVID-19-positive; 2011 intra-pandemic COVID-19-negative; and 2800 pre-pandemic. COVID-19-positive patients were older, with higher surgical risk, more advanced pathologies, and higher P-POSSUM values (1.79% vs. 1.09%, p < 0.001, in both the COVID-19-negative and control cohort). 30-day mortality in the COVID-19-positive, intra-pandemic COVID-19-negative and pre-pandemic cohorts were: 12.9%, 4.6%, and 3.2%. The P-POSSUM predictive values in the three cohorts were, respectively: AUC 0.88 (95% CI 0.81–0.95), 0.89 (95% CI 0.87–0.92), and 0.91 (95% CI 0.88–0.93); β value 0.97 (95% CI 0.74–1.2), 0.99 (95% CI 0.82–1.16), and 0.78 (95% CI 0.74–0.82); sensitivity 83% (95% CI 61–95), 91% (95% CI 84–96), and 89% (95% CI 80–94); and specificity 81% (95% CI 74–87), 76% (95% CI 74–78), and 80% (95% CI 79–82). Conclusion: The P-POSSUM score showed a good predictive capacity for postoperative mortality in COVID-19-positive patients submitted to emergency general and digestive surgery. Highlights: P-POSSUM score has a good predictive capacity in COVID-19-infected patients. Postoperative mortality after emergency gastrointestinal surgery can be effectively estimated. The P-POSSUM score allows the identification of "high risk" patients during the pandemic. The predictive capacity of this known surgical score exceeds other scores used during the pandemic.